SUN-585 Associations Between UCP1(rs1800592),UCP2(rs6593366) and UCP3(rs1800849) with Fasting Glucose, Body Mass Index, and Energy Expenditure - Figueroa-Vega, Nicté (J Endocr Soc, 2020)
Background: The uncoupling proteins (UCPs) belong to the mitochondrial inner membrane anion carrier superfamily and play an important role in energy homeostasis. UCP-1 is expressed mostly in brown adipose tissue (BAT) and act in the thermogenesis and regulation of energy expenditure. UCP-2 has a role in the metabolism of fatty acids direct and indirectly path insulin secretion. UCP-3 is specific of skeletal muscle and BAT and may affects the adaptive and translocation of fatty acids. Genetic polymorphisms in these proteins have been associated with obesity, as rs1800592 (-3826 A/G) in UCP-1 gene. The rs659366 (-866GA) UCP-2 has being associated with high expression of its RNAm, decrease of obesity risk, and increase of energy expenditure. The rs1800849 (-55CT) UCP-3 has been associated with low risk of type 2 Diabetes Mellitus, but its association with body mass index is controversial. Objective: To analyze the association of the polymorphisms rs1800592 UCP-1, rs659366 UCP-2, and rs1800849 UCP-3 with BMI and resting energy expenditure (REE). Material and Methods: We included 120 subjects with BMI>30kg/m(2) and 100 subjects with BMI between18.5 -24.9 kg/m(2), aged 20 to 50 years. Anthropometric data were recorded and the REE was measure for indirect calorimetric. Fasting glucose and lipid profile were assessed. Leptin, insulin and acylated-ghrelin were quantified by ELISA. Genomic DNA was extracted using comercial kit. Genotyping for three polymorphisms was performed by allelic discrimination using Taqman probes. Results: All the three polymorphisms of UCPs showed distribution in accordance with Hardy-Weinberg equilibrium. The weight, BMI, glucose, triglycerides, leptin, insulin, HOMA-IR, and REE levels were signitifcantly higher in obese subjects. There was a strong correlation between REE with BMI (r=0.42, p<0.00001) and with insulin levels (r=0.229, p=0.001) in all group. No differences in genotypic and allelic frequencies of rs1800592 UCP-1, rs659366 UCP-2 and rs180084 UCP-3 polymorphisms between obese and lean subjects. No differences among the genotypes rs1800592 UCP-1 and rs1800849 UCP-3 with metabolic variables. In rs659366 UCP-2 polymorhism, the REE and glucose concentrations were lower in carriers of rs659366AA genotype (F=3.11, p=0.046; F=2.97, p=0.053, respectively) in whole group. In obese subjects with rs659366AA UCP-2 genotype, the REE was significantly low (F=4.15, P=0.017). Conclusion. In this work the obese subjects with rs659366AA genotype had low REE. We found low glucose concentrations in the carries of rs659366 AA genotype.